[3-({(E)-2-[(4-Fluorophenyl)carbamothioyl]hydrazinylidene}methyl)- 4-hydroxybenzyl]methyltriphenylphosphonium chloride - Sinniah, S.K.; Tan, K.W.; Sim, K.S.; Ng, S.W.; Tiekink, E.R.T. (International Union of Crystallography, 2011)
The cation in the title salt, C(33)H(28)FN(3)OPS(+)center dot Cl(-), is highly twisted with the phosphonium group occupying a position almost normal to the central hydroxylbenzene ring [P-C-C-C tosrsion angle = -100.9 (3)degrees], and with the hydrazone substituent twisted out of the plane [C-C-C-N torsion angle = 13.1 (4)degrees]. The fluorobenzene ring is twisted out of the plane of the adjacent thiourea residue, forming a dihedral angle of 51.69 (10)degrees. The configuration about the C=N bond [1.281 (4) angstrom] is E, the O-H and N-H hydrogen atoms are syn, and in the thiourea residue, the N-H hydrogen atoms are anti, allowing for the formation of an intramolecular N-H center dot center dot center dot N hydrogen bond. In the crystal, dimeric aggregates mediated by N-H center dot center dot center dot S bonds are formed, which are linked to the Cl(-) anions by O-H center dot center dot center dot Cl hydrogen bonds. The four-component aggregates are linked into a three-dimensional structure by C-H center dot center dot center dot Cl interactions.